PERBANDINGAN VALIDITAS ANALISIS MOYERS DAN ANALISIS SITEPU PADA MAHASISWA SUKU MINANG FAKULTAS KEDOKTERAN GIGI UNIVERSITAS ANDALAS - Monica Wihanda Kurnia; Nur Indrawati Lipoeto; Hidayati Hidayati (Faculty of Dentistry Universitas Andalas, 2014)
Background: Malocclusion is a deviation from normal occlusion of teeth, and the majority of malocclusion cases occur in the stage of mixed dentition. There are several methods in the analysis of mixed dentition, two of which are Moyers analytical method and Sitepu analytical method. This study aims to determine the comparison of validity between Moyers analysis and Sitepu analysis when used in Minang ethnic students at FKG UNAND. Methods: This study used an analytical descriptive method. The sample consisted of 50 Minang ethnic students at Dentistry Faculty (FKG) of Andalas University selected by purposive sampling technique. The data analysis used Mann-Whitney test for maxilla and Independent t-test for mandible. Result: The results show the existence of differences in the validity between Moyers analysis and Sitepu analysis if used to Minang ethnic students at FKG UNAND. Sitepu analysis was valid in maxilla and mandible (p > 0.05), while Moyers analysis was only valid in maxilla (p > 0.05), and in mandible showed the value of p < 0.05. Conclusion: The conclusion of this study is that there is validity difference between Moyers analysis and Sitepu analysis in Minang ethnic students of FKG UNAND, Sitepu method is valid in maxilla and mandible, while Moyers analysis is only valid in maxilla.